The Laboratory Diagnosis of Lyme Borreliosis: Guidelines from the Canadian Public Health Laboratory Network - Canadian Public Health Laboratory Network (Canadian Journal of Infectious Diseases and Medical Microbiology)
Lyme borreliosis is uncommonly seen in Canada. Most cases have occurred in close proximity to small geographical areas where infected ticks have become established. Although few cases are seen, thousands of patients are tested yearly. Unless patients are carefully selected and an appropriately sensitive and specific testing algorithm is applied, large numbers of patients without Lyme borreliosis will be incorrectly diagnosed. The Canadian Public Health Laboratory Network has developed the present guidelines to assist physicians in assessing patients for Lyme borreliosis, and to help guide the choice and interpretation of laboratory testing.